Induced mutaton as a source of variability for cold tolerance of irrigated rice at the germinaton stage - Raimondi, Juliana Vieira (2020)
Tolerance to low temperatures in the germinaton stage of rice cultvars is an eﬀectve control method for avoiding the damage caused by this phenomenon of abiotc and unpredictable nature. This study was carried out to evaluate the efciency of induced mutaton in the generaton of genetc variability for cold tolerance at the germinaton stage. M2 seed families were treated with gamma rays and subjected to low temperature for 28 days. The respectve lines and cultvars untreated with gamma rays were used for comparison to certfy the presence of genetc variability in M2 families. Great amount of variability for germinaton rate was observed in all M2 families, as well as for length of the coleoptle and radicle. M2 populatons of SC 319, SC 333, SC 342, SC 213, Epagri 106, Epagri 107, Epagri 108 and Epagri 109 presented higher tolerance to low temperatures than the untreated line and cultvars. It was possible to select rice plants with tolerance to low temperatures during germinaton. It can be concluded that the induced mutaton is eﬀectve in generatng variability for this feature.